Antioxidant activity of ecoenzyme derived from Siamese orange peel (Citrus nobilis) at different fermentation duration - Anak Agung Ayu Radismarani Putri; Pande Ayu Naya Kasih Permatananda; I Gde Suranaya Pandit; Asri Lestarini (Acta Biochimica Indonesiana, 2024)
Background: Ecoenzyme is an organic fermentation product derived from fruit peel waste, offering zero-waste system benefits along with antibacterial, insecticidal, and cleaning properties. Kintamani, a major producer of Siamese oranges (Citrus nobilis) in Bali, generates significant orange peel waste suitable for ecoenzyme production. However, the antioxidant potential of ecoenzymes remains poorly studied. Objective: This study aimed to evaluate the antioxidant activity of ecoenzymes produced from Kintamani Siamese orange peel waste, enhancing their beneficial value. Methods: This experimental study assessed and compared the antioxidant activity of ecoenzymes fermented for 10 days, 1 month, and 3 months. Antioxidant activity was measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, with results expressed as IC50 values. Results: Antioxidant activity, classified according to Blois criteria, showed the highest activity after three months of fermentation. The mean IC50 values were 53,612 ppm for 10-day fermentation; 18,753 ppm for 1-month fermentation; and 6,727 ppm for 3-month fermentation. Conclusion: Ecoenzymes derived from Kintamani Siamese orange peel waste exhibited very weak antioxidant activity across all fermentation durations. A 3-month fermentation period is recommended to achieve the highest antioxidant activity compared to shorter durations.